2006
DOI: 10.1002/hed.20418
|View full text |Cite
|
Sign up to set email alerts
|

First clinical case of boron neutron capture therapy for head and neck malignancies using 18F‐BPA PET

Abstract: Although only 1 patient has shown complete regression and additional long-term follow-up should be required to assess this treatment, we believe that head and neck tumors are suitable for BNCT and that such excellent results will have a great impact on patients in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 68 publications
1
56
0
Order By: Relevance
“…Higher amounts suitable for treatment have also not shown significant toxicity. 17,[37][38][39] In all 3 patients, the amount of 10 B measured in the tumor by PGRS was lower than anticipated, not reaching the value defined as ''favorable'' in the protocol. This is in clear contradiction to all published data reporting 10 B-concentration ratios of tumor to normal tissues of >2.…”
Section: L-para-boronophenylalaninementioning
confidence: 65%
See 2 more Smart Citations
“…Higher amounts suitable for treatment have also not shown significant toxicity. 17,[37][38][39] In all 3 patients, the amount of 10 B measured in the tumor by PGRS was lower than anticipated, not reaching the value defined as ''favorable'' in the protocol. This is in clear contradiction to all published data reporting 10 B-concentration ratios of tumor to normal tissues of >2.…”
Section: L-para-boronophenylalaninementioning
confidence: 65%
“…This is in clear contradiction to all published data reporting 10 B-concentration ratios of tumor to normal tissues of >2. 17,27,[37][38][39] It might be argued that due to the high metabolic activity of the liver, the uptake of BPA in liver is higher than in brain, skin or other relevant organs at risk leading to decreased ratios between metastases and liver. This hypothesis however is not supported by the data published by Pinelli et al, who reported a 10 B-concentration ratio between metastasis/liver of 5.9 in the first patient treated in Pavia.…”
Section: L-para-boronophenylalaninementioning
confidence: 99%
See 1 more Smart Citation
“…10 (3). It was used in clinical trials to treat glioblastoma and melanoma (10 -12) and in combination with BSH to treat squamous cell carcinoma of head and neck (13,14).…”
Section: Animals and Tumorsmentioning
confidence: 99%
“…Results from a few small series (11)(12)(13) and case reports (14,15) suggest that BNCT is effective in the treatment of locally recurrent head-and-neck cancer, and that most tumors respond to BNCT.…”
Section: Introductionmentioning
confidence: 99%